Supplementation with oral vitamin D3 and calcium during winter prevents seasonal bone loss: a randomized controlled open-label prospective trial - Meier, Christian; Woitge, Henning W.; Witte, Klaus; Lemmer, Björn; Seibel, Markus J. (Journal of bone and mineral research, 2004)
Bone metabolism follows a seasonal pattern with high bone turnover and bone loss during the winter. In a randomized, open-label 2-year sequential follow-up study of 55 healthy adults, we found that supplementation with oral vitamin D3 and calcium during winter abolished seasonal changes in calciotropic hormones and markers of bone turnover and led to an increase in BMD. Supplementation with oral vitamin D3 and calcium during the winter months seems to counteract the effects of seasonal changes in vitamin D and thus may be beneficial as a primary prevention strategy for age-related bone loss. Introduction: Bone metabolism follows a seasonal pattern characterized by high bone turnover and bone loss during winter. We investigated whether wintertime supplementation with oral vitamin D3 and calcium had beneficial effects on the circannual changes in bone turnover and bone mass. Materials and Methods: This prospective study comprised an initial observation period of 12 months (“year 1”), followed by an intervention during parts of year 2. Fifty-five healthy subjects living in southwestern Germany (latitude, 49.5° N) were randomized into two groups: 30 subjects were assigned to the treatment group and received oral cholecalciferol (500 IU/day) and calcium (500 mg/day) during the winter months of year 2 (October-April), while 25 subjects assigned to the control group obtained no supplements. Primary endpoints were changes in calciotropic hormones [serum 25(OH)D, 1,25(OH)2D, and parathyroid hormone], markers of bone formation (serum bone-specific alkaline phosphatase) and of bone resorption (urinary pyridinoline and deoxypyridinoline), and changes in lumbar spine and femoral neck BMD. Results: Forty-three subjects completed the study. During year 1, calciotropic hormones, markers of bone turnover, and BMD varied by season in both groups. During the winter months of year 1, bone turnover was significantly accelerated, and lumbar spine and femoral BMD declined by 0.3-0.9%. In year 2, seasonal changes in calciotropic hormones and markers of bone turnover were either reversed or abolished in the intervention group while unchanged in the control cohort. In the subjects receiving oral vitamin D3 and calcium, lumbar and femoral BMD increased significantly (lumbar spine: +0.8%, p = 0.04 versus year 1; femoral neck: +0.1%, p = 0.05 versus year 1), whereas controls continued to lose bone (intervention group versus control group: lumbar spine, p = 0.03; femoral neck, p = 0.05). Conclusions: Supplementation with oral vitamin D3 and calcium during winter prevents seasonal changes in bone turnover and bone loss in healthy adults. It seems conceivable that annually recurring cycles of low vitamin D and mild secondary hyperparathyroidism during the winter months contributes, at least in part and over many years, to age-related bone loss. Supplementation with low-dose oral vitamin D3 and calcium during winter may be an efficient and inexpensive strategy for the primary prevention of bone loss in northern latitudes.